Breaking the "Insecurity Trap"? How Violence and Counter-violence are Perpetuated in Elite Power Struggles - Andreas Mehler (German Institute of Global and Area Studies (GIGA), 2008)
Half a century after independence, African elites, at least those in conflict-ridden countries, often live in constant fear for their life. Real or invented coup attempts, political assassinations, beatings of opposition leaders, the distribution of death lists, etc. have a profoundly traumatizing and self-perpetuating effect. Purges, not least in the security apparatus, are not uncommon, particularly after changes in government, be they peaceful or violent. These purges come at a cost: the excluded elites are frequently tempted to use violence to come back into the 'dining room' - and the excluding government tries to prevent reentry by all means. This contribution draws a dense picture of elite (in)security in three African countries (Central African Republic, Côte d'Ivoire and Liberia). A comparative analysis of elite security needs and devices is undertaken, permitting the author to draw some preliminary conclusions: The ineffectiveness of state institutions (presidential guards, etc.) in breaking the insecurity trap by providing special elite-protection services is obvious. The record of private security services is most debatable and efforts by international actors need to be looked at more closely: UN peacekeepers can be effective when they are sufficient in number and have the appropriate mandate. The record of French interventions in former colonies has over time become ever more ambivalent and has lost any preventive meaning. – – Ein halbes Jahrhundert nach der Unabhängigkeit leben die Eliten zumindest der durch Konflikte zerrissenen Staaten in beständiger Lebensangst. Tatsächliche oder erfundene Putschversuche, politische Attentate, das Verprügeln von Oppositionspolitikern, die Verbreitung von Todeslisten etc. haben tief traumatisierende und sich selbst verstärkende Effekte. Säuberungen, vor allem im Sicherheitsapparat, sind nicht unüblich, gerade nach friedlichen oder gewaltsamen Regierungswechseln. Diese Säuberungen produzieren Kosten: ausgeschlossene Eliten sind oft geneigt, Gewalt anzuwenden, um ins 'Speisezimmer' zurückzugelangen, und die Regierung versucht, diese Wiederkehr mit allen Mitteln zu verhindern. Der vorliegende Beitrag zeichnet ein dichtes Bild der (Un)Sicherheit von Eliten in drei afrikanischen Staaten (Zentralafrikanische Republik, Côte d'Ivoire und Liberia). Vorgenommen wird eine komparative Analyse von Bedarfen und Mechanismen der Elitensicherheit, um zu folgenden vorläufigen Ergebnissen zu kommen: offensichtlich ist die Ineffizienz staatlicher Einrichtungen (Präsidialgarden etc.), durch spezifischen Elitenschutz die Unsicherheitsfalle zu durchbrechen. Die Bilanz privater Sicherheitsdienste ist umstritten und die Bemühungen internationaler Akteure müssen näher betrachtet und differenziert werden: UN-Friedenstruppen können effizient sein, wenn sie in ausreichender Zahl und mit dem richtigen Mandat auftreten. Die Bilanz französischer Interventionen in Exkolonien ist dagegen allmählich immer ambivalenter geworden und hat mittlerweile jegliche vorbeugende Wirkung verloren.
Keywords: 300; Africa; elites; security; Central African Republic; Côte d'Ivoire; Liberia